HBEGF, SRA1, and IK: Three cosegregating genes as determinants of cardiomyopathy - Friedrichs, Frauke; Zugck, Christian; Rauch, Gerd-Jörg; Ivandic, Boris; Weichenhan, Dieter; Müller-Bardorff, Margit; Meder, Benjamin; El Mokhtari, Nour Eddine; Regitz-Zagrosek, Vera; Hetzer, Roland; Schäfer, Arne; Schreiber, Stefan; et al.

(untitled) (Genome Research, 2009)
Human dilated cardiomyopathy (DCM), a disorder of the cardiac muscle, causes considerable morbidity and mortality and is one of the major causes of sudden cardiac death. Genetic factors play a role in the etiology and pathogenesis of DCM. Disease-associated genetic variations identified to date have been identified in single families or single sporadic patients and explain a minority of the etiology of DCM. We show that a 600-kb region of linkage disequilibrium (LD) on 5q31.2-3, harboring multiple genes, is associated with cardiomyopathy in three independent Caucasian populations (combined P-value = 0.00087). Functional assessment in zebrafish demonstrates that at least three genes, orthologous to loci in this LD block, HBEGF, IK, and SRA1, result independently in a phenotype of myocardial contractile dysfunction when their expression is reduced with morpholino antisense reagents. Evolutionary analysis across multiple vertebrate genomes suggests that this heart failure-associated LD block emerged by a series of genomic rearrangements across amphibian, avian, and mammalian genomes and is maintained as a cluster in mammals. Taken together, these observations challenge the simple notion that disease phenotypes can be traced to altered function of a single locus within a haplotype and suggest that a more detailed assessment of causality can be necessary.